Role of Natural Compounds in Inflammation and Inflammatory-Related Diseases - Maione, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The papers reported here will contribute to proposing new insights into the mechanisms of several conditions, as well as suggesting new diagnostic alternatives and therapeutic targets in widespread pathologies such inflammation and inflammatory-based diseases. The discovery of the new is, as always, anchored in recourse to the old.